2021
DOI: 10.1016/j.cell.2021.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Microglia jointly degrade fibrillar alpha-synuclein cargo by distribution through tunneling nanotubes

Abstract: Microglia are the CNS resident immune cells that react to misfolded proteins through pattern recognition receptor ligation and activation of inflammatory pathways. Here, we studied how microglia handle and cope with a-synuclein (a-syn) fibrils and their clearance. We found that microglia exposed to a-syn establish a cellular network through the formation of F-actin-dependent intercellular connections, which transfer a-syn from overloaded microglia to neighboring naive microglia where the a-syn cargo got rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
172
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(210 citation statements)
references
References 75 publications
6
172
2
Order By: Relevance
“…Microglia were juxtaposed to nerve cells with α-synuclein inclusions. Unlike what has been reported previously [ 65 , 66 ], we failed to observe α-synuclein- or pFTAA-positive inclusions in microglia. Nerve cells labelled by pFTAA were also pS129 α-synuclein-positive.…”
Section: Discussioncontrasting
confidence: 99%
“…Microglia were juxtaposed to nerve cells with α-synuclein inclusions. Unlike what has been reported previously [ 65 , 66 ], we failed to observe α-synuclein- or pFTAA-positive inclusions in microglia. Nerve cells labelled by pFTAA were also pS129 α-synuclein-positive.…”
Section: Discussioncontrasting
confidence: 99%
“…In particular, TNTs have been found in vitro to convey fibrillar α-synuclein (α-syn) cargoes from α-syn –overloaded astrocytes to microglia where it is degraded. Similarly, it was recently reported that α-syn-overloaded microglia have the capacity to form TNTs, as observed both in vitro and in vivo, allowing them to discharge their excessive α-syn aggregate contents to neighboring naive microglia, which take care of their clearance [ 117 ]. Beyond their role in α-syn degradation, the TNTs that connect naive microglia to affected microglia have also been shown to mediate the transfer of mitochondria to these affected microglia, thereby preventing cell death and inflammation [ 117 ].…”
Section: Focus On An Organ: the Brain Role Of Intercellular Communica...mentioning
confidence: 97%
“…Similarly, it was recently reported that α-syn-overloaded microglia have the capacity to form TNTs, as observed both in vitro and in vivo, allowing them to discharge their excessive α-syn aggregate contents to neighboring naive microglia, which take care of their clearance [ 117 ]. Beyond their role in α-syn degradation, the TNTs that connect naive microglia to affected microglia have also been shown to mediate the transfer of mitochondria to these affected microglia, thereby preventing cell death and inflammation [ 117 ]. Finally, TNT-mediated transfer of misfolded protein aggregates between neurons has been documented in vitro in several studies [ 59 , 74 , 75 ].…”
Section: Focus On An Organ: the Brain Role Of Intercellular Communica...mentioning
confidence: 97%
“…The study suggests that transfer of mitochondria from healthy cells via TNTs reverses the cellular stress in early stage of apoptosis. A recent work [ 112 ] has shown that α-synuclein protofibril-induced defects in cellular degradation machineries in microglia enhance cell to cell networks via TNTs to transfer the burden of proteotoxic aggregates to neighbouring cells. The study has also shown that mitochondrial shuffling and sharing of proteotoxic burdens via TNTs alleviate ROS levels and rescue cells from ROS-induced apoptosis.…”
Section: Association Of Tunnelling Nanotubes With Oxidative Stress Apoptosis and Mitochondrial Homeostasismentioning
confidence: 99%
“…Recently, another study has reported that Arp2/3 negatively regulates biogenesis of TNTs in CAD cells [ 5 ]. Another recent study [ 112 ] has shown that inhibition of ROCK (using chemical inhibitor Y-27632), a downstream signalling molecule of Rho/Rac/Cdc42, promotes biogenesis of TNTs. The study has indicated that ROCK inhibition promotes TNT formation via Myosin II regulated f-actin modulation.…”
Section: Rho Gtpase Related Signals Counteract Apoptosis Via Tunnelling Nanotubesmentioning
confidence: 99%